Xerxés, Ariadné, Trimalchio és a többiek: Opera és antikvitás – a kortárs rendezői és szerzői koncepciók tükrében - Csehy, Zoltán (Studia Litteraria, 2015)
This study provides the synoptic treatment of Ancient themes in modern opera. The first part reflects on the classical operas reinterpreted by contemporary Hungarian directors (Balázs Kovalik, Róbert Alföldi, Ferenc Anger); the second part deals with the new contemporary works inspired by Ancient texts. The main questions focus on the tension between the Ancient material and the strategies of reinterpretation, on the selffashioning of the author and on the examination of the original texts’ cultural identity. The most important strategies of the reanimation of Ancient cultural or textual ambient are: a) reconstruction (Melis, Orff), b) plasticity and common presence of the multifaced myths (Bussotti, Birtwistle), c) ritualisation (Dillon, Furrer), d) fragmentation (Maderna), e) „exposure” of the myth or the well-known story (Martinů, Dallapiccola, Turnage), f) utilisation of the Ancient context for the purposes of the ”emancipation” (Harrison).